LIE DETECTION SYSTEM BY USING RESTING-STATE EEG AND P300-BASED GKT - Mohd Rashid, Ahmad Syauqi (Universiti Teknologi PETRONAS, 2017)
In the 20th Century, the advancement in technology has sparked interest for scientist in researching further on the methods of detecting lies. One of the most popular methods which is the polygraph has now been replaced with a new approach, which is the P300-based Guilty Knowledge Test (GKT). The purpose of this study is to introduce a new approach in the P300-based GKT by researching on the possible methods for performing this sort of test and combining the elements which can yield a more positive yet accurate result. For the evaluation of the methods which are being introduced in this study, several subjects undergo the designed GKT paradigm and their brain signals are recorded before after the test is conducted. The analysis of results will implement wave power features of theta wave power and alpha wave power. The results yield a higher theta wave power and alpha wave power for the guilty group than the innocent group for the analysis of resting state EEG data collected before and after the GKT paradigm.